Ecology, Epidemiology and Disease Management of Ralstonia syzygii in Indonesia - Safni, Irda; Subandiyah, Siti; Fegan, Mark (Frontiers in Microbiology, 2018)
Ralstonia solanacearum species complex phylotype IV strains, which have been primarily isolated from Indonesia, Australia, Japan, Korea and Malaysia, have undergone recent taxonomic and nomenclatural changes to be placed in the species Ralstonia syzygii. This species contains three subspecies; Ralstonia syzygii subsp. syzygii, a pathogen causing Sumatra disease of clove trees in Indonesia, Ralstonia syzygii subsp. indonesiensis, the causal pathogen of bacterial wilt disease on a wide range of host plants, and Ralstonia syzygii subsp. celebesensis, the causal pathogen of blood disease on Musa spp. In Indonesia, these three subspecies have devastated the cultivation of susceptible host plants which have high economic value. Limited knowledge on the ecology and epidemiology of the diseases has hindered the development of effective control strategies. In this review, we provide insights into the ecology, epidemiology and disease control of these three subspecies of Ralstonia syzygii.